EFEK GLOBALISASI DALAM PERSPEKTIF PENDIDIKAN - Ade Zaenudin; Yazid Hady (STAI ALHIKMAH Jakarta, 2021)
AbstractGlobalization can be interpreted as a condition where human interaction is not separated by space and time. In this condition, the competition for life is getting tougher because it does not only intersect with the local community but with the global community. This study focuses on analyzing the effects of globalization on education programs in Indonesia. This study uses qualitative research methods with literature studies. Based on the results of literature research, globalization has implications for the face of the world of education, start shifting from tradition to modernization, from social spiritual to commercial, and from local to universal. The researcher also identified the presence of eight programs as an effect of globalization in the world of education, the inclusion of foreign languages as learning materials, the presence of foreign language/literature majors, program collaboration between cross-country educational institutions, collaboration with foreign donor agencies, the existence of an international level Student Competency Assessment, establishment of cross-border educational institutions, cross-country lecturer exchanges, and student exchanges between countries.AbstrakGlobalisasi bisa dimaknai sebagai sebuah keadaan dimana interaksi manusia sudah tidak bersekatkan ruang dan waktu. Dalam kondisi ini, persaingan hidup semakin ketat karena tidak hanya bersinggungan dengan komunitas lokal saja tapi jauh lebih luas yaitu dengan komunitas global. Penelitian ini fokus menganalisis bagaimana efek globalisasi terhadap program Pendidikan di Indonesia. Penelitian ini menggunakan metode penelitian kualitatif dengan studi literatur. Berdasarkan hasil penelitian literatur ditemukan fakta bahwa globalisasi berimplikasi pada wajah dunia pendidikan mulai dari pergeseran tradisi ke modernisasi, sosial spiritual ke komersial, dan dari lokal ke universal. Peneliti juga mengidentifikasi hadirnya delapan program sebagai efek globalisasi di dunia pendidikan, yaitu masuknya bahasa asing sebagai materi pembelajaran, hadirnya jurusan bahasa / sastra asing, kerjasama program antar lembaga pendidikan lintas negara, kerjasama dengan lembaga donor luar negeri, adanya Asesmen Kompetensi Siswa tingkat internasional, pendirian lembaga pendidikan lintas negara, pertukaran dosen lintas negara, dan adanya pertukaran pelajar antar negara.